PERBANDINGAN EFEKTIVITAS GLENOHUMERAL MOBILIZATION DAN PRONE RAISE EXERCISE TERHADAP PERUBAHAN LINGKUP GERAK SENDI DAN NYERI SHOULDER PENDERITA SHOULDER IMPINGEMENT SYNDROME - Nur Achirda; Hanif Arko Aji; Abdurahman Berbudi Bowo Laksono (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Abstract Background: Shoulder impingement syndrome commonly abbreviated as SIS is a push between the acromion and the humeral tuberosity on the tendon of the supraspinatus muscle. The occurrence of rotator cuff muscle weakness, muscle balance, glenohumeral dysfunction, aging process and inflammation of the tendon or bursa are the causes of impingement syndrome. Shoulder impingement syndrome is associated with overuse of the shoulder. Research Methods: This research design uses a Quasi-Experimental research design with a Two Group Pre Test-Post Test Design approach. This study consisted of 15 respondents per intervention group, namely the USGM and USPRE groups. So the samples taken in this study were 30 respondents. Results: The results of the study on statistical tests of differences in LGS and VAS pain before and after USGM and USPRE interventions with Paired t-test, obtained p value less than 0.05 that there was a significant increase in the two interventions. The results of the different LGS and VAS values ​​after the intervention with the Independent Sample T-test test, yielded a p value of more than 0.05 of 0.500 min – 0.923 max, which means that there is no significant difference in increasing joint range of motion and decreasing pain. Conclusion: Both the USGM and USPRE interventions have been shown to increase the range of motion of the joints and reduce pain in patients with SIS. There was no significant difference in effectiveness between USGM and USPRE in increasing joint range of motion and reducing pain.